Study of the Effect of Penetrant Temperature Variations on Corrosion Sensitivity of 7075 Alumnium material using the Liquid Penetrant Test Method at PT. Dirgantara Indonesia (IAe) - Yudhistira, Prayogi; Prabowo, Imam; Yunardi, Yongki (Journal of Metallurgical Engineering and Processing Technology, 2025)
Non Destructive Test is a testing and analysis method carried out to evaluate and detect differences in characteristics or defects that arise in materials, components, structures or systems without causing damage to the part being tested. Liquid Penetrant Test is a Non-Destructive Test method using Liquid Penetrant containing Fluorescent by utilizing power capillarity which is the ability of the penetrant liquid to enter the gap discontinuity and developer work to lift the liquid back up which penetrates into cracks so that defects and corrosion can be detected. The purpose of this test is to determine discontinuities in the fabricated material by using 3 variations of penetrant temperature 5℃, 10℃ - 38℃, and 75℃ using 2 pieces of 7075 Aluminum material. Experiments carried out at normal temperatures (10℃-38℃) show clear indications of the material. while experiments using temperatures of 5℃ and 75℃ will make the indication on the material unclear (false indication) due to various factors such as viscosity, dwell time, penetration, developing.